Novel Fast-Setting and Mechanically-Strong Calcium Phosphate Pulp-Capping Cement with Metformin Release to Enhance Dental Pulp Stem Cells - Mohammad Alenizy; Abdullah Alhussein; Nader Almutairi; Ibrahim Ba-Armah; Tao Ma; Suping Wang; Nageswara R. Pilli; Maureen A. Kane; Michael D. Weir; Abraham Schneider; Hockin H. K. Xu (Bioengineering)
Traditional pulp-capping materials like mineral trioxide aggregate (MTA) offer excellent biocompatibility and sealing, but limitations such as prolonged setting time, low bioactivity, and high costs persist. Metformin, with its potential in craniofacial regeneration, could enhance dentin synthesis by targeting pulp cells. This study aimed to: (1) develop a calcium phosphate cement with chitosan (CPCC) with improved physio-mechanical properties; (2) incorporate metformin (CPCC-Met) to assess release; and (3) evaluate human dental pulp stem cells (hDPSCs) response. CPCC was mixed at different powder-to-liquid ratios to evaluate physio-mechanical properties compared to MTA. The optimized CPCC formulation was loaded with 0, 50, 100, and 150 µg of metformin to measure release and assess hDPSCs attachment and proliferation (1, 4, and 7 d) via live/dead imaging and SEM. One-way ANOVA was used for statistical analysis. Results showed CPCC at a 3.25:1 ratio significantly reduced setting time to 41.5 min versus 123 min for MTA (p < 0.05). Metformin release correlated with concentration, and SEM confirmed the presence of a porous, hydroxyapatite-rich surface. Cell viability was consistently high across groups (>93% at 1 d, >95% at 4 d, ≈98% at 7 d), with no significant differences (p > 0.05). These findings suggest that the novel CPCC-Met demonstrates promise as a fast-setting, cost-effective pulp-capping material, offering metformin delivery to enhance dentin repair.